The oretical and methodological basis of ways to increase the efficiency of agricultural production - Abdirashidov Temurbek Abdirashid oglu (THE INNOVATION ECONOMY, 2026)
This article explores the theoretical and methodological foundations of increasing agricultural productivity in the Kashkadarya region. The study employs economic-statistical analysis, comparative analysis, and SWOT analysis methods. The findings show that, although crop yields have been increasing year by year, the efficiency of resource utilization remains lower compared to other regions of Uzbekistan. The research highlights rational use of land and water resources, the introduction of innovative agro-technologies, and the development of cluster-based production as the key factors in improving agricultural efficiency